Quantidade e qualidade de água em nascentes e cursos d'água no município de Jacutinga, MG - Amâncio, Diego Vipa (2021)
The multiple uses of water resources from hydromineral sources, especially their water quality, were the main objectives proposed in this work. Human activities cause changes in the soil and end up interfering with the water quality. The UPGRH GD6 – Affluents of the Mogi-Guaçu and Pardo Rivers of the Minas Gerais Water Management Institute (IGAM), in particular the Mogi River, site of this study. Six sampling points were chosen, four springs and two watercourses. Based on the assumption, the aim of this work was: i) Characterization and water quality using the Scott & Knott Test; ii) Water production and characterization of trace elements associated with the Scott & Knott Test; iii) Principal component analysis for the water quality variables. The monitoring period was from June 2017 to November 2018, resulting in thirteen samplings. We used a tipping bucket rain gauge to monitor the rainfall in the region during the period of the study. For the analysis of water quality, we used simple samples, using the procedures for collection and preservation of samples, according to the National Guide for Collection and Preservation of Samples. After the samplings, we conducted the analysis in the Hydrology laboratory of the Water Resources Department at the Federal University of Lavras. The respective analysis were: Biochemical Oxygen Demand (DBO), Dissolved Oxygen (OD), Potential of Hydrogen (pH), Turbidity (TURB), Temperature (T), Nitrate (NO3-), Phosphate (PO43-), Total Solids (ST), Thermotolerant Coliforms (CT). The heavy metals were Aluminium (Al), Bromine (Br), Copper (Cu), Chromium (Cr), Iron (Fe), Manganese (Mn), Nickel (Ni), Silver (Ag) and Zinc (Zn). We compared the results for the water quality variables with DN COPAM CERH 01/08 – Class 2. The principal components analysis was carried out based on the results found in the laboratory analysis. We used the statistical language R to work on the values found. Based on the results, within the analysed water quality variables, only the DBO, pH and ST variables had a behavioural pattern among the studied springs, whereas in C1 and C2, only the variable OD presented distinct values. The final values of the IQA in N2 and N4 presented better results, classified as Good. For the watercourses, the final values were Average. The springs showed good Specific Yields during monitoring, a situation in which the soils of the respective points presented good recharge. Nevertheless, C1 showed a low recharge compared to C2. Based on the results, we observed values greater than allowed for Copper, Iron, Manganese and Zinc in all monitoring. Regarding the ACP, we observed that within the formed groups, the water quality variables that most affected the monitoring points were NO3- and PO43-, Zn and Ni, associated with agricultural activities, Fe and Mn resulting from local mineralogy and DBO, OD and CT, originating from organic loads from untreated domestic effluents, agricultural activities and intensive livestock farming. Based on the results, we concluded that the main impacting factors within the monitoring might be associated with agricultural activities in the monitoring areas.